Validity and reliability of an optoelectronic system to measure movement velocity during bench press and half squat in a Smith machine - Muniz-Pardos, B.; Lozano-Berges, G.; Marin-Puyalto, J.; Gonzalez-Agüero, A.; Vicente-Rodriguez, G.; Casajus, J. A.; Garatachea, N. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2020)
The purpose of this study was to determine the validity and reliability of a camera-based optoelectronic system to measure movement velocity during bench press and half squat at different load intensities. A total of 22 active males (age: 28.2 ± 3.9 years; one-repetition maximum bench press: 77.9 ± 19.0 kg; one-repetition maximum half squat: 116.6 ± 22.5 kg) participated in this study. After an initial one-repetition maximum testing session, participants performed five repetitions for each load (40%, 60% and 80% one-repetition maximum) and exercise (bench press and half squat) on a Smith machine in the second testing session. A third testing session was used for the test-retest reliability study. Time, displacement and mean propulsive velocity were simultaneously determined by the reference method (T-Force system) and the Velowin system. In bench press, ordinary least products regression analysis revealed low fixed biases for mean propulsive velocity at 40%, time at 60% and displacement at 80% one-repetition maximum (intercept = 0.065 m s-1, -28.02 ms and 0.87 cm, respectively). In half squat, low fixed biases were also detected for mean propulsive velocity at 40% and 80% one-repetition maximum (intercept = -0.040 and 0.023 m s-1, respectively), time at 40% and 60% one-repetition maximum (intercept = -53.05 and -101.85 ms, respectively) and displacement at 60% one-repetition maximum (intercept?=?-1.95?cm). Proportional bias was only observed for mean propulsive velocity at 80% bench press. In half squat, there was proportional bias for time and mean propulsive velocity at 40% one-repetition maximum, and also for time at 60% one-repetition maximum. The reliability test showed low and comparable fixed and proportional biases between systems across exercises and intensities. Velowin confirmed to be a valid and reliable system to measure movement velocity across a wide range of intensities (40%-80% one-repetition maximum) for two basic strength exercises through a robust statistical approach. Velowin would provide coaches and trainers with a suitable, affordable and easy-to-use equipment capable of measuring movement velocity in various exercises at different load intensities.